Nazwy cech człowieka w filmach animowanych a kompetencja językowa dzieci - Bąk, Marzena (Dydaktyka Polonistyczna, 2016)
The aim of the following paper is to analyse vocabulary that denominates human qualities in terms of physical, mental, characterological features as well as in terms of interests, passions and attitude towards another person. Animated cartoons broadcasted between July 2011 and December 2012 on the channel Teletoon+ were the source material for the research. During the excerption of lexical items only those which denominate human qualities (the items were nouns, verbs and adjectives) were taken into account. Variety of names which denominate human qualities shows that the authors of dialogue scripts very often use names which are known to older youth and adults. Therefore, the meaning of most of them is not understood by younger viewers. Moreover, the lexis is most often offensive and stigmatizing other people, full of invectives, pejorative phrases which are very often radical and rude. Thus it is not adjusted to the age and language competence of the youngest viewers.